'Marine fungi' and 'marine-derived fungi' in natural product chemistry research: Toward a new consensual definition. Issue 4 (October 2016) - Pang, Ka-Lai; Overy, David P.; Jones, E.B. Gareth; Calado, Maria da Luz; Burgaud, Gaëtan; Walker, Allison K.; Johnson, John A.; Kerr, Russell G.; Cha, Hyo-Jung; Bills, Gerald F.
Abstract: The discovery of new natural products from fungi isolated from substrata in marine environment has increased dramatically over the last few decades, cumulating in over 1000 new metabolites. The term 'marine-derived fungi' is used extensively in these reports, and it refers to the environment from which the fungi are isolated, in contrast to the classical ecological definition of 'marine fungi' as obligate and facultative inhabitants of the marine environment. In a significant number of reports, the origins of substrata or habitat relationships of strains referred to as 'marine-derived fungi' are unknown or whether a seawater medium was used for their isolation. In August 2014, a workshop held at the University of Prince Edward Island, Canada was convened to discuss a series of topics related to marine fungal natural product research. A central discussion topic was "What constitutes a marine fungus?" There was a general agreement that a review of the definition of a marine fungus would be beneficial to the marine fungal natural product community, together with an evaluation of the suitability and relevance of the use of the term 'marine-derived fungi'. We here propose a revised, broad definition of a marine fungus as 'any fungus that is recovered repeatedly from marine habitats because: 1) it is able to grow and/or sporulate (on substrata) in marine environments; 2) it forms symbiotic relationships with other marine organisms; or 3) it is shown to adapt and evolve at the genetic level or be metabolically active in marine environments'. Highlights: Novel natural products of marine fungi have increased dramatically in recent years. The term 'marine-derived fungi' is used in most reports in natural chemistry discipline. 'Marine' status of the fungi is questionable in some reports, especially mangrove endophytes. Metagenomics and genome sequencing, etc. can be used to identify fungi of a marine origin. A broad definition of marine fungi based on physiology, ecology and molecular biology is proposed.